Local and systemic safety of deproteinized calf blood extract injection: hypersensitivity, hemolysis, local tolerance, and acute intravenous toxicity in rodents and rabbits - Qin, Guodong; Zhao, Pengfei (Frontiers in Pharmacology, 2026)
IntroductionDeproteinized calf blood extract injection (DCBEI) is widely applied in neurology and wound care, but systematic preclinical safety data are scarce. Because it is administered parenterally, assessment of immunogenicity, hemocompatibility, local tolerance, and acute toxicity is essential to meet regulatory standards.MethodsA focused safety package was developed, comprising: (i) active systemic anaphylaxis (ASA) in Hartley guinea pigs (n = 24, 4 groups); (ii) in-vitro hemolysis in rabbit erythrocytes, spectrophotometrically measured at 545 nm over 0.25–3 h; (iii) local tolerance in New Zealand White rabbits (n = 4 per regimen) after single or 6-day repeated intravenous (ear-vein) or intramuscular (quadriceps) dosing, assessed macroscopically and by histopathology; and (iv) acute intravenous toxicity in Kunming mice (n = 50, 5 groups, 3.075–6.150 g kg-1 total solids), with logistic regression used to estimate LD50 and 95% CI.ResultsNo DCBEI-treated animals developed ASA reactions ≥ grade 2 (0/6), while all ovalbumin controls showed severe grade 4 responses. Hemolysis remained ≤4.88% across all concentrations and timepoints, consistent with saline controls and below the 5% non-hemolytic threshold. Local tolerance was favorable, with macroscopic scores of 0 and no histopathological abnormalities after single or repeated administration. Acute dosing produced a dose-dependent mortality curve, yielding an LD50 of 4.35 g kg-1 (95% CI 4.03–4.69).ConclusionThis route-relevant dataset establishes a compact preclinical safety foundation for DCBEI, supporting its continued clinical use and guiding future investigations into long-term toxicology and translational risk management.